2020
DOI: 10.3390/insects11080500
|View full text |Cite
|
Sign up to set email alerts
|

Stingless Bee Honey: Evaluating Its Antibacterial Activity and Bacterial Diversity

Abstract: Stingless bee honey (SBH) is an astounding ‘miracle liquid’ with countless medicinal properties for various diseases such as gastroenteritis, cataracts, as well as for wound-healing. However, knowledge regarding it is still rather scarce. Henceforth, it is intriguing for us to contemplate on the less-studied stingless bee and its honey in particular. First and foremost, the antimicrobial ability of honey from eight different stingless bee species was tested to further proven its health benefit. Homotrigona fim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 46 publications
2
71
2
3
Order By: Relevance
“…Contemporary science has found that most traditional uses have great potential as an added value in modern medicine and has considered this honey to have a higher medicinal value than A. mellifera honey [ 20 ]. Meliponini honey, also called pot-honey, has organoleptic and physicochemical characteristics, which are completely different from that produced by A. mellifera [ 21 , 22 ]. This is due to the different technology used by the bees: A. mellifera remove moisture by using their wings and add enzymes in order to digest sugars and conserve honey.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary science has found that most traditional uses have great potential as an added value in modern medicine and has considered this honey to have a higher medicinal value than A. mellifera honey [ 20 ]. Meliponini honey, also called pot-honey, has organoleptic and physicochemical characteristics, which are completely different from that produced by A. mellifera [ 21 , 22 ]. This is due to the different technology used by the bees: A. mellifera remove moisture by using their wings and add enzymes in order to digest sugars and conserve honey.…”
Section: Discussionmentioning
confidence: 99%
“…Trigona spinipes , unlike Tetragonisca angustula , uses for nest construction mud and animal feces [ 30 , 31 ], which would explain the large number of sequences of Escherichia coli and Alcaligenes faecalis , two common species in the digestive tract of mammals. In fact, Trigona spinipes honey is popularly considered "spoiled" [ 30 ], which could be due to the presence of contaminants, as seen in microbiological analyzes of honey from different species [ 13 , 32 , 33 ]. On the other hand, Tetragonisca angustula uses only wax to make its nests, in addition to small amounts of propolis (coming from plant resin) to seal cracks [ 36 ], which would explain the detection of microbes associated with aerial part of plants ( Xanthomonas axonopodis and Sphingomonas melonis [ 34 , 35 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Belonging to the Apidae family (including bumblebees, honey bees, carpenter bees and orchid bees) and Meliponini tribe with about 500 species, they can be found in most tropical or subtropical regions of the world and are characterized as eusocial bees and non-stinger, building their nest most often in tree hollows [11]. To date, very few studies have been done with the stingless bees microbiome, focusing on the gut and honey microbiome [12][13][14]. Whether in stingless bees or honey bees, little is explored regarding the microbiome associated with their nests.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have evaluated the effects of honey on cancer (Afrin et al, 2018b;Mohammed et al, 2020), diabetes (Sahlan et al, 2020) and dyslipidemias (Ramli et al, 2019), showing significant ameliorative effects. Likewise, antimicrobial effects have been reported when using honey (Rosli et al, 2020).…”
Section: Anti-inflammatory and Antioxidant Effects Of Honeymentioning
confidence: 91%
“…Honey can also contain toxic compounds including pesticides (Chiesa et al, 2018;El Agrebi et al, 2020), heavy metals (Bartha et al, 2020;Bosancic et al, 2020) and antibiotics (Barrasso et al, 2018) due to environmental pollution in honey harvesting areas. Bacterial contamination is another relevant factor that must be taken into consideration to ensure that honey is suitable for therapeutic purposes; for instance, the presence of Clostridium botulinum spores have been previously identified in honey samples (Nevas et al, 2002;Rosli et al, 2020). In this context, the use of medical-grade honey (MGH) guarantees its safety for clinical application (Hermanns et al, 2019).…”
Section: Honey Biosafety For Clinical Applicationsmentioning
confidence: 99%